Investigation of Particle Motion in a Swirling Fluidized Bed using Particle Imaging Velocimetry - Chin Swee Miin, Chin Swee Miin (Universiti Teknologi Petronas, 2012)
Fluidized bed is an advanced technology which possesses a number of characteristics ideal for a wide variety of industrial applications due to its advantages over many existing technologies in industry. However, conventional fluidized bed used in most of the industry today has certain drawbacks which affect the efficiency of the bed. Swirling Fluidized Bed (SFB) is one of the evolutions of fluidized bed, which has the potential for solving many drawbacks of conventional fluidized bed. Nonetheless, limited research has been done on this bed as compared to other versions of fluidized bed, thus a lot of problems occurred when come to scaling up to commercial size. This was mainly due to the lack of understanding of the particle dynamic characteristics of the bed. Most of the research studied the overall bed characteristics especially the pressure drop. There is limited study on the velocity and particle motion. Furthermore, available literature concentrates only analytical model and simulation results. No published experimental information is available for the analysis of the particle velocity. Thus, the objectives of the present study are to investigate particle motion in a swirling fluidized bed and to study the effect of air flow rate, bed weight, blade angle, particle size and particle shape on the fluidized particle velocity. The particle motion of the SFB is studied by using Particle Imaging Velocimetry (PIV) in an experimental model of SFB. The experiments were carried out with bed weight varied from 500 g to 1500 g with only stable swirling regime was studied and the velocity of the top layer particles was evaluated. From the study, it is found that the particle velocity increases with air flow rate at shallow bed and as bed weight is increased, particle velocity decreases by higher occurrence of vigorous bubbles. It is also observed that particle velocity decreases less than 18% with 3o increment in the blade angle. Small particle yields lower minimum swirling air superficial velocity which means preferable for saving energy, but with constraint of shallow bed. Particle with elongated shape possesses short range of stable swirling due to easier occurrence of bubbling. The results of this project give a better understanding of the particle velocity and motion which can provide a great contribution towards designing the fluidized bed especially for catalyst activity, coating and drying.